2014
DOI: 10.22146/ijc.21261
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antidiabetic Activities of Extract and Isolated Flavonoid Compounds from <i>Artocarpus altilis</i> (Parkinson) Fosberg

Abstract: The antidiabetic activity test through a mechanism of inhibition of α-glucosidase enzyme was studied against ethanol, n-hexane, ethyl acetate and n-butanol fractions of ethanol extract of Artocarpus altilis (Parkinson) Fosberg (Moraceae) leaves and four flavonoid compounds isolated from ethyl acetate extracts of A. altilis. Ethyl acetate fraction has strongest antidiabetic activity compared to ethanol, n-hexane, and n-butanol fractions with IC50values5.98,6.79, 440.18and14.42μg/mL, respectively. Four flavonoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
(14 reference statements)
0
4
0
2
Order By: Relevance
“…Meanwhile, the positive control, acarbose showed a strongest inhibitory activity with IC50 of 6.79 ppm (Rante et al, 2019). In another study, the α-glucosidase enzyme inhibition assay of A. altilis leaf extract showed that ethanol extract and ethyl acetate fraction have antidiabetic activity stronger than quercetin as positive control with IC50 values of 6.79 μg/mL, 5.98 μg/mL and 11.60 μg/mL, respectively (Lotulung et al, 2014).…”
Section: Artocarpus Altilismentioning
confidence: 98%
“…Meanwhile, the positive control, acarbose showed a strongest inhibitory activity with IC50 of 6.79 ppm (Rante et al, 2019). In another study, the α-glucosidase enzyme inhibition assay of A. altilis leaf extract showed that ethanol extract and ethyl acetate fraction have antidiabetic activity stronger than quercetin as positive control with IC50 values of 6.79 μg/mL, 5.98 μg/mL and 11.60 μg/mL, respectively (Lotulung et al, 2014).…”
Section: Artocarpus Altilismentioning
confidence: 98%
“…Flavonoids extracted from Artocarpus altilis also exhibit inhibition activity against α-glucosidase, with the inhibition type being a non-competitive one [71]. Another source of flavonoids, such as Samama plant extract, has been demonstrated to inhibit α-glucosidase activity [72].…”
Section: Interaction Of Flavonoids With Digestive Enzymesmentioning
confidence: 99%
“…Artikel ini menyajikan perkembangan terkini yang lebih komprehensif dari tahun 2000 hingga 2020 meliputi aspek etnobotani di Indonesia, studi fitokimia, farmakologi, dan toksikologi. Aspek aktivitas farmakologi yang dikaji seperti aktivitas antidiabetes, antioksidan, pelindung radiasi UV, antiatherosklerosis, antihipertensi, antibakteri, antijamur, antiinflamasi, antikanker, kardioprotektif, antimalaria, serta mampu memperbaiki fungsi ginjal (Adaramoye & Akanni, 2014;Andriani, 2013;Hafid dkk., 2016;Haryoto & Widowati, 2018;Lan et al, 2013;Lotulung et al, 2014;Riasari dkk., 2017;Siddesha et al, 2011;Tiraravesit et al, 2015).…”
Section: Pendahuluanunclassified
“…Senyawa AC-31 merupakan senyawa antidiabetes yang paling poten dibandingkan dengan AC-51, AC-33 dan siklokommunol dengan nilai IC50 masing-masing sebesar 15,73; 24,41; 49,49; dan 72,20 μg/mL. Senyawa AC-31 menghambat enzim α-glukosidase secara tidak kompetitif dalam studi kinetik metode Lineweaver-Burk (Lotulung et al, 2014).…”
Section: A Antidiabetesunclassified